Overexpression of Endometrial Estrogen Receptor-Alpha in The Window of Implantation in Women with Unexplained Infertility - Dorostghoal, Mehran; Ghaffari, Hamid-O-Allah; Marmazi, Farideh; Keikhah, Narjes (International journal of fertility & sterility, 2018)
Failure in the endometrial receptivity may account for a significant number of infertility cases including unexplained infertility in women. Reduction in the endometrial estrogen receptor-alpha (ER-α) expression during implantation may be a critical event that coincides with the expression of specific genes and the formation of a receptive endometrium. The aim of the present study was to assess the expression of ER-α in the mid-secretory phase in the endometrium of women with unexplained infertility. This case-control study was carried out on randomly selected fertile (n=10) and infertile (n=16) women whose source of infertility remained unexplained. We evaluated the expression of ER-α and glycodelin- A (GdA) through mRNA level measurement with real-time polymerase chain reaction (PCR) in the endometrium of fertile women and patients suffering from unexplained infertility and fertile women. Endometrial biopsies of each subject were collected during a single menstrual cycle 7 days after the peak of luteinizing hormone (LH+7). Endometrial expression level of ER-α was significantly (P<0.05) higher in the patients with unexplained infertility compared to the control. Significantly (P<0.05) lower levels of GdA expression were seen in women with unexplained infertility. A statistically non-significant negative correlation was observed between ER-α and GdA mRNA expression. Our findings demonstrate that reduction in the endometrial GdA expression is associated with elevated expression of ER-α in mid-luteal phase. Disruption in the endometrial ER-α expression, which leads to defects in uterine receptivity, may contribute to unexplained infertility.